Cerita Rakyat Jawa Barat Sebagai Pembentuk Literasi Moral pada Peserta Didik Kelas 4 di SD Weninggalih 02 - Amelia Rahman; Fadhia Salsabila Hazami; Alifiah Choirunnisa; Siti Jaojah Wiratna; Muhammad Syachtiko; Hana Fauzia Izzati; Tazkiyah .; Adetya Chairul Anhar; Tegar Ananda Pradana; Bobi Fauzi Waryanto (Jurnal Ilmiah Wahana Pendidikan, 2023)
This study discusses the forms of moral values that exist in folklore in West Java. Moral is the teaching of good or bad deeds and behavior. Moral can be used as a measuring tool to determine the good and bad character or behavior of a person. Folklore is a story that develops and lives in a society. Folklore in ancient times was spread by word of mouth, although at this time many folk tales were written. In a folk tale, there is a moral value of character that is depicted through the story or its characters. These moral values can be used as examples in the daily life of grade 4 students at Weninggalih 02 Elementary School. The method used in this research is descriptive qualitative. The data sources in this study are five folk stories from West Java. The results of this study are forms of moral values read by students who show attitudes towards fellow human beings including (1) helping each other, (2) being honest, (3) respecting others, (4) being responsible, and (5) respecting parents